’Traditionele’ leiders en instellingen in Somaliland. Een Somalische staat in opbouw - Renders, Marleen (Afrika Focus, 2006)
This article addresses the prominence of ’traditional’ leaders and institutions in the Somaliland’s "success-story" of political reconstruction after a violent conflict. Can the Somaliland experience be replicated and serve as a model for other cases of problematic statehood? Through an analysis of the Somaliland case, the article shows that one can not simply ’use’ traditional leaders and institutions. They are not a-political entities or concepts. They are adaptable and have a dynamic of their own. The ’traditional’ order is profoundly connected with ’non-traditional’ orders i.e. ’modem’ political leaders and institutions. How both develop and interact is contingent upon an aggregate of factors which develop over a long period of time. This set offactors include so-called ’structural’ ones as well as ones that are more ’agency’-related. This aggregation of factors makes the Somaliland experience difficult to replicate. ’Traditional’ leaders and institutions are not magic bullets, not a one- fits-all in cases of problematic statehood. They should not be viewed as a-political components of some ’appropriate governance technology’ that will provide leaders and institutions supposedly adapted to a timeless ’African situation and culture ’. Key Words: Somalia, Somaliland, ’Traditional’ Leaders, Post-War Reconstruction, Institutions